Epidermal NLRP10 contributes to contact hypersensitivity responses in mice. Issue 8 (16th June 2016) - Damm, Anna; Giebeler, Nives; Zamek, Jan; Zigrino, Paola; Kufer, Thomas A.
Abstract : Many NLR proteins contribute to innate and adaptive immune responses. Using a novel conditional knock‐out mouse line we show that epidermal NLRP10 contributes to contact hypersensitivity (CHS) responses. This work reveals a novel biological function of NLRP10 in skin inflammatory responses. Abstract : The nucleotide binding and oligomerization domain‐like receptor (NLR) protein NLRP10 is highly expressed in the epidermis and contributes to cell‐autonomous responses against invasive bacteria. To investigate the role of NLRP10 in inflammatory responses of the skin we analyzed the effect of full‐body and keratinocyte‐specific depletion of NLRP10 in croton oil‐induced irritant contact dermatitis (ICD) and 1‐fluoro‐2, 4‐dinitrobenzene (DNFB)‐induced contact hypersensitivity (CHS) in mice. Nlrp10 −/− mice were phenotypically normal and skin repair after wounding was not affected by lack of NLRP10. Similarly, we did not detect a contribution of NLRP10 to the ICD response induced by croton oil. In contrast, Nlrp10 −/− mice showed significantly reduced inflammation in the DNFB‐induced CHS response as compared to control animals. Microscopic analysis revealed significantly reduced numbers of CD4 + and CD8 + T cells in the infiltrates of animals lacking NLRP10 expression after CHS challenge. Epidermis‐specific deletion of Nlrp10 by keratin‐14 promotor driven Cre‐recombinase was sufficient to account for this phenotype, although lymphocyte recruitment seemed to be unaltered in animals lacking NLRP10 expression in keratinocytes. Taken together, we provide evidence that NLRP10 contributes to T‐cell‐mediated inflammatory responses in the skin and highlight a physiological role of NLRP10 in epidermal keratinocytes.